PENINGKATAN HASIL BELAJAR PPKn MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI SISWA KELAS IV SD NEGERI 011 BERINGIN MAKMUR KECAMATAN KERUMUTAN - ', Ambari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
SD Negeri 011 Beringin Makmur, especially in the fourth grade, KKM to subjects who haveditatapkan PPKn is by KKM is 65. Particularly in the fourth grade SD Negeri 011 BeringinMakmur PPKn low student learning outcomes. It can be seen from the students after the testin midterm average value of only 61.5. Based on the preliminary study authors, the lowstudent learning outcomes PPKn caused by several things, the strategies used in teaching theteacher does not comply with the demands of learning and students during lessons PPKnfrequency only ask very little because the material is only presented in the form of lectures.The purpose of this study is to improve learning outcomes in subjects PPKn through theimplementation of inquiry learning model SD Negeri 011 Beringin Makmur fourth gradestudents. This research is a classroom action through the stages of planning, implementingaction, observation and reflection. Design research is the model cycle of improvementplanning, implementing action, observation and reflection. The subjects were students ingrade IV SD Negeri 011 Beringin Makmur with the number of 30 people, including 15 womenand 15 men. While the object of the research is PPKn student learning outcomes, the dataused in this study focuses on learning outcomes data PPKn only. From the results of theaction, can be seen learning outcome Civics students from before action is taken (preliminarydata) cycle I and after the action on the second cycle by improving student learning outcomesthat have been achieved, known completeness class on preliminary data only 15 or (50 %) ofall students and after repair in the first cycle has increased to 26 people or 87% of the totalclass IV student SD Negeri 011 Beringin Makmur. After the improvement in cycle II to beincreased to 27 students or 90%.